Comparative quality assessment of esophageal examination with transnasal and sedated endoscopy - Crews, Nicholas R.; Gorospe, Emmanuel C.; Johnson, Michele L.; Wong Kee Song, Louis-Michel; Katzka, David A.; Iyer, Prasad G. (Endoscopy International Open, 2017)
Background Unsedated transnasal esophagoscopy (TNE) may offer a less expensive, mobile alternative to sedated esophagogastroduodenoscopy (EGD) for evaluations of reflux related complications. Comparisons of imaging quality by these methods are lacking.Methods Two reviewers evaluated videos of TNE and EGD procedures, performed during a community randomized study comparing endoscopic techniques. Subjects were randomized to EGD, TNE in endoscopy suite, or TNE in mobile research unit. Endoscopic quality was assessed using a validated scoring tool.Results In total, 115 videos (58 EGD, 28 endoscopy suite TNE, and 29 mobile TNE) were reviewed. Overall quality scores for TNE and EGD were excellent without a statistically significant difference (P = 0.30). There were no differences in gastroesophageal junction (GEJ) visualization scores, though EGD scored higher in esophageal passage (P < 0.05) and TNE scored higher in esophageal intubation (P < 0.05). There was no significant difference in any quality score between mobile TNE and gastrointestinal suite TNE.Conclusion Esophageal assessment with TNE or EGD was comparable in overall quality and GEJ visualization. TNE quality was not affected by procedure location. TNE is a feasible option for endoscopic assessment of reflux complications.